2018
DOI: 10.1080/21642583.2018.1477634
|View full text |Cite
|
Sign up to set email alerts
|

Autonomous robots for harsh environments: a holistic overview of current solutions and ongoing challenges

Abstract: This paper presents a holistic overview of robotics and autonomous systems developed for applications in harsh environments where interactions with robots are difficult to model due to reasons such as dynamics, uncertainty, complexity and unpredictability. Robots of different characteristics and designs are required to perform different tasks within these environments. A number of classes of robots emerge as particularly favoured by the research community for solving challenging problems in difficult environme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 71 publications
(35 citation statements)
references
References 30 publications
0
35
0
Order By: Relevance
“…Kang et al conducted a stress and buckling analysis of a ray-type hull structure of a new underwater glider based on carbon fiber, being lighter and stronger than duralumin [ 17 ]. Wong et al reported that operability under sea ice conditions, localization without GPS, vehicles based on multi thrusters, and intelligent manipulation skills have been the key technologies of autonomous robotics for deep-sea conditions [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Kang et al conducted a stress and buckling analysis of a ray-type hull structure of a new underwater glider based on carbon fiber, being lighter and stronger than duralumin [ 17 ]. Wong et al reported that operability under sea ice conditions, localization without GPS, vehicles based on multi thrusters, and intelligent manipulation skills have been the key technologies of autonomous robotics for deep-sea conditions [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, when the paradigm is introduced to the manufacturing system, each factor is addressed at every stage of the product life cycle-design phase, manufacture phase, usage phase scenarios, UGVs are often required to perform in harsh environments, that are unreachable or too dangerous for humans, such as in Fukushima Daiichi event [12]. These environments can be irradiated, flooded, have spreading fire source, high explosion or structural collapse risk [13]. Commonly in these situations, no initial knowledge about the operating environment is given to the autonomous mobile agent.…”
Section: Introductionmentioning
confidence: 99%
“…The modern UAVs have the ability to carry a variety of payloads' equipment to perform desired missions with realtime processing. The UAV market in experiencing an exponential growth due to the wide range of the practical applications in hazardous, uncertain and threatening areas [2]. Recently, due to the integration of internet of things and cloud technologies with the UAV the application scenarios of UAVs are becoming more and more advance [3].…”
Section: Introductionmentioning
confidence: 99%